2011
DOI: 10.1021/ja2059999
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Formation of Cyclopentenone Derivatives via the Unique Cycloaddition of α,β-Unsaturated Phenyl Esters with Alkynes

Abstract: Oxygen-containing organic compounds, such as ethers, carboxylates, and carbamates, have recently received increasing attention because of their newly discovered applications as electrophiles in cross-coupling reactions via transition metal-catalyzed C-O bond activation. However, no cycloaddition reaction involving their C-O bond activation has been demonstrated thus far. The present study developed a Ni(0)-catalyzed unique [3+2] cycloaddition reaction of α,β-unsaturated phenyl esters with alkynes in (i)PrOH to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 56 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…T ransition metal-catalyzed coupling of alkynals/alkynones has become a powerful method for efficient construction of allylic alcohol derivatives in current organic chemistry [1][2][3] . Recent development by employing various transition metal catalysts such as Ti 4 , Ni [5][6][7][8][9][10][11][12][13][14][15][16][17][18] , Rh [19][20][21][22][23][24] , Ir 25 , Ru [26][27][28] , and Pd 29,30 in combination with a variety of coupling components and reducing/alkylative agents has greatly expanded its scope and applications. Among them, the nickel-catalyzed coupling of π systems pioneered by Mori 5,8 , Montgomery 6,7,10 , and Jamison 9,15 , is particularly attractive and offers a broad substrate scope and good functional group compatibility.…”
mentioning
confidence: 99%
“…T ransition metal-catalyzed coupling of alkynals/alkynones has become a powerful method for efficient construction of allylic alcohol derivatives in current organic chemistry [1][2][3] . Recent development by employing various transition metal catalysts such as Ti 4 , Ni [5][6][7][8][9][10][11][12][13][14][15][16][17][18] , Rh [19][20][21][22][23][24] , Ir 25 , Ru [26][27][28] , and Pd 29,30 in combination with a variety of coupling components and reducing/alkylative agents has greatly expanded its scope and applications. Among them, the nickel-catalyzed coupling of π systems pioneered by Mori 5,8 , Montgomery 6,7,10 , and Jamison 9,15 , is particularly attractive and offers a broad substrate scope and good functional group compatibility.…”
mentioning
confidence: 99%
“…Evaluation of electronic and loading effects did not lead to significant improvements.S urprisingly,s ubsequent experiments using PhB(OH) 2 as the activator revealed that various alcoholic solvents,i ncluding primary,s econdary,a nd tertiary alcohols,dramatically promoted the reaction (entries [12][13][14][15][16][17][18][19]. Ethanol was optimal, affording the desired product in 90 % yield (entry 17).…”
mentioning
confidence: 99%
“…These results suggest that both PhB(OH) 2 and EtOH are essential for good reactivity.Further 1 HNMR tracing experiments suggested ap ossible coordination of EtOH to PhB-(OH) 2 could be formed in the excess of EtOH, which could play an in situ Brønsted acid role.C onsidering that nickel easily catalyze the direct couplings of alkenes and carbonyls to form ar igid oxanickellacycle, [16] we proposed that herein either PhB(OH) 2 or the coordinated complex of PhB(OH) 2 with EtOH could facilitate the ring opening of the oxanickellacycle through protonation, [17] thereby leading to subsequent b-hydride elimination and reductive elimination to provide the desired product and regenerate PhB(OH) 2 and the nickel catalyst (Scheme 6).…”
mentioning
confidence: 99%
“…Subsequently, Urabe and co‐workers described an iron‐mediated intramolecular reductive cyclization of dienedioates to synthesize bicyclic ketoesters 8. Very recently, Ogoshi and Ohashi developed a unique Ni 0 ‐catalyzed [3+2] cycloaddition reaction of α,β‐unsaturated phenyl esters with alkynes in i PrOH to yield cyclopentenone derivatives 9…”
Section: Methodsmentioning
confidence: 99%